(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The hormonal regulation of the sexual cycle is a complex interplay of various hormones that orchestrate the physiological changes in the reproductive system. This article delves into the mechanisms by which hormones such as estrogen, progesterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) regulate the menstrual cycle in females, as well as the roles of testosterone in male reproductive physiology. The article outlines the phases of the sexual cycle, the feedback mechanisms involved, and the implications of hormonal imbalances on reproductive health. Understanding these hormonal interactions is essential for addressing issues related to fertility, menstrual disorders, and other reproductive health concerns.